1995
DOI: 10.1042/bj3060801
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the type-IVA cyclic AMP-specific phosphodiesterase RD1 as a membrane-bound protein expressed in cerebellum

Abstract: An antiserum was generated against a dodecapeptide whose sequence is found at the C-terminus of a cyclic AMP (cAMP)-specific, type-IVA phosphodiesterase encoded by the rat 'dunc-like' cyclic AMP phosphodiesterase (RD1) cDNA. This antiserum identified a single approximately 73 kDa protein species upon immunoblotting of cerebellum homogenates. This species co-migrated upon SDS/PAGE with a single immunoreactive species observed in COS cells transfected with the cDNA for RD1. Native RD1 in cerebellum was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
169
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(189 citation statements)
references
References 41 publications
20
169
0
Order By: Relevance
“…3), as labeled by antibody C-PDE4A (batch 271). Again, they are known to be PDE4A5 and PDE4A1, respectively (Shakur et al, 1995;Ye et al, 1997). In addition, there was a minor, 102-kDa band that has been shown previously to be a presently uncharacterized PDE4A variant termed PDE4AX (Ye et al, 1997).…”
Section: Effects Of Repeated Antidepressant Treatments On Pde4a and ␤mentioning
confidence: 82%
See 1 more Smart Citation
“…3), as labeled by antibody C-PDE4A (batch 271). Again, they are known to be PDE4A5 and PDE4A1, respectively (Shakur et al, 1995;Ye et al, 1997). In addition, there was a minor, 102-kDa band that has been shown previously to be a presently uncharacterized PDE4A variant termed PDE4AX (Ye et al, 1997).…”
Section: Effects Of Repeated Antidepressant Treatments On Pde4a and ␤mentioning
confidence: 82%
“…1), as labeled by the PDE4A-selective antibody. Based on the results of previous studies, these are identified as PDE4A5 and PDE4A1, respectively (Shakur et al, 1995;Ye et al, 1997).…”
Section: Figmentioning
confidence: 99%
“…These were performed as described previously [21,24,35]. Briefly, increasing concentrations of high-speed pellet protein from COS cells, transfected with various PDE-expressing plasmids, were analysed by immunoblotting.…”
Section: Relative V Max Determinationsmentioning
confidence: 99%
“…To define K m values, data from PDE assays were analysed by computer fitting to the hyperbolic form of the Michaelis-Menten equation using an iterative least-squares procedure (Ultrafit ; with Marquardt algorithm, robust fit, experimental errors supplied ; Biosoft). Relative V max values could be calculated using the Michaelis equation and the experimentally derived K m values, as described previously [35].…”
Section: Relative V Max Determinationsmentioning
confidence: 99%
“…For example, whereas phosphorylation of the amino terminus of the PDE4D3 variant by PKA increases its activity (21)(22)(23), PDE4D3 is inactivated by extracellular signal-regulated kinase-mediated phosphorylation in vivo (24). PDE4A1, PDE4D, and PDE2A are localized in the Golgi apparatus (25)(26)(27)(28)(29)(30)(31), and PDE3B is associated with the endoplasmic reticulum via its amino-terminal hydrophobic domain (32). Thus, it is intriguing that alterations of the cyclic nucleotide-hydrolyzing activity of PDEs by the phosphorylation and compartmentalization of several signaling molecules such as PDEs, AKAPs, and PKA would be involved in the modulation of the subcellular signaling of cyclic nucleotides.…”
mentioning
confidence: 99%